Scoping review of infectious disease prevention, mitigation and management in passenger ships and at ports: mapping the literature to develop comprehensive and effective public health measures - Lemonia Anagnostopoulos; Sotirios Vasileiadis; Leonidas Kourentis; Zacharoula Bogogiannidou; Ioanna Voulgaridi; Gordon Nichols; Fani Kalala; Matthaios Speletas; Christos Hadjichristodoulou; Varvara A. Mouchtouri; the EU HEALTHY SAILING project (Tropical Medicine and Health)
Abstract Background With various infectious disease risks to passenger ship travellers, guidance for infectious disease prevention, mitigation and management (PMM) exists. Emerging infections and emergencies necessitate updated, context-specific guidelines and practices. New evidence for infection PMM must be translated into guidance for governmental authorities and the passenger ship industry. Under the European HEALTHY SAILING project, we conducted a scoping review of publications in PubMed, Scopus and grey literature for scientific articles, regulations, guidelines and policies describing infectious disease PMM in seaports, cruise, ferry, expedition and river cruise ships between 1990 and 2023. Main findings Of 620 publications most were peer-reviewed articles (57.7%) and technical guidance (27.9%), followed by reports/other documents (9.1%), industry guidance (3.4%) and legislation (1.9%). Half (50.5%) of all publications addressed respiratory illnesses, fewer addressed gastroenteritis (11.5%), Legionnaire’s (6.1%), other vaccine-preventable (3.2%), vector-borne (1.6%) and sexually transmitted (1.0%) diseases. Most publications focus on infectious disease in seagoing cruise ships (75.7%) compared to ferries, expedition and river cruise ships (26.6%, 16.9%, 16.3%, respectively). Fewer publications addressed seaports (39.0%), shore-side personnel (19.7%) and port communities (2.4%). Most literature was published between 2020 and 2023 (50.2%) with a peak addressing respiratory illnesses (264 publications) during this period. A trend in volume and type was observed based on public health emergencies associated with the publication year. Conclusions Peer-reviewed articles and guidance primarily address respiratory and gastrointestinal illnesses, seagoing cruise ships and onboard populations. Gaps on the following topics exist: other infectious disease types; other passenger ship types; land-based personnel and port communities. Future research could assess risk factors and PMM measure effectiveness considering vaccine-preventable, vector-borne and sexually transmitted diseases. The evidence-base should be strengthened to produce guidelines targeting specificities of seaports, ferries, expedition and river cruise ships. Developing guidelines to standardise passenger ship outbreak investigation reporting could help evaluate PMM measure effectiveness, the impact of passenger ship travel on port communities and vice versa. Modern passenger ship experiences—from educational to elderly focused cruising—present diverse public health risks, requiring continuous efforts by public health authorities and the shipping industry. While outside the review’s scope, measures may impact travellers’ mental health, necessitating strategies when designing and implementing PMM measures.